Water quality assessment of the Asata River catchment area in Enugu Metropolis, Southeast Nigeria. (September 2016) - Osinowo, Olawale Olakunle
Abstract: Hydrogeochemical mapping of the Asata River Catchment area in the Enugu metropolis, southeast Nigeria was carried out in order to assess the quality of the surface and groundwater and based on the analyses of the hydrogeochemical data, establish the level of chemical contaminations which inhibit the availability of potable water in the area. Forty (40) water samples comprising five (5) springs, nineteen (19) surface (streams/rivers) and sixteen (16) groundwater (well/borehole) samples were collected and analysed for the presence and degree of contamination of nine (9) major chemical contaminants. Hydrochemical analyses indicate that Electrical Conductivity (EC) which has a linear relationship with Total Dissolved Solid (TDS) ranges between 015 and 887 μS/cm, pH between 4.4 and 8.3, nitrate (NO3 − ) ranges between 40 and 130 mg/l and chloride (Cl − ) between 7 and 130 mg/l. The concentrations of the dissolved chemical constituents defined the pollution trend and the rate of dispersion of contaminants. The degree of contaminants followed a simple trend, where the level of contamination of the dissolved chemical constituents is least in sampled spring water, with measured chemical constituents of EC, pH, NO3 − and Cl − range from 15 to 354 μS/cm; 6.4–6.5; 4.0–70 mg/l and 8–36 mg/l, respectively. However, the value of the measured chemical constituent of EC, pH, NO3 − and Cl − gradually increases down the stream in both the surface (63–354 μS/cm; 4.5–7.7; 7.1–110 mg/l; 8–41 mg/l) and groundwater (56–531 μS/cm; 4.5–7.5; 40–130 mg/l; 7–130 mg/l), respectively. Noticeable peaks in contamination levels characterised sections of the study area where human population or their activities is highest. The result of the hydrogeochemical mapping indicate that Enugu coal mine operation, the industrial activities, fertilizer applied to plants cultivated on river banks and domestic human wastes which are indiscriminately dumped along river channels are the major sources of chemical contamination in the Asata River catchment area. An adequate water resource management scheme is urgently needed to rescue the shallow regolith aquifer from being permanently damaged. Acts such as construction of uncased toilet pits and septic tanks into the thin shallow regolith aquifer, application of inorganic fertilizers along river bank farms and indiscriminate dumping of untreated industrial and human wastes should also be discouraged. Highlights: Identify the major chemical contaminants present in ground and surface water of Asata River catchment in Enugu metropolis. Determine the sources of these chemical contaminants. Establish the water contamination trend across the Asata water catchment area. Map the contamination plumes and provide necessary recommendations.